Analisis Faktor yang Berhubungan dengan Kepatuhan Hand Hygiene pada Perawat di RSUD Sungai Lilin - Martilopa, Iis; Gustina, Erma; Ekawati, Dianita; Wahyudi, Arie (Universitas Baiturrahim, 2024)
The incidence of nosocomial infections can actually be prevented if health care facilities consistently implement the PPI program. Infection Prevention and Control is an effort to ensure protection for everyone against the possibility of contracting infection from sources in the general public and when receiving health services at various health facilities. The research targets were nurses who worked at Sungai Lilin Regional Hospital. The aim of this research is to determine the factors related to hand hygiene compliance among nurses at Sungai Lilin Regional Hospital. This research was conducted in February 2024 with a research sample of 57 people. The sampling technique used a total population of 57 samples. This research is quantitative research with a cross sectional approach. The test was carried out using bivariate analysis with the chi-square test. Based on the research results, namely gender P-Value: 0.400, employment status P-Value: 0.250, length of service P-Value: 0.169, knowledge P-Value: 0.000, attitude P-Value: 0.000, availability of P-facilities -Value: 0.038 and the role of the PPI Team P-Value: 0.003. It can be concluded that there is a relationship between knowledge, attitudes, availability of facilities and the role of the PPI Team with hand hygiene compliance among nurses. It is hoped that there will be support from management in the form of giving awards such as certificates to nurses who comply with hand hygiene properly so that nurses at Sungai Lilin Hospital will have a more positive attitude in carrying out hand hygiene..